2010
DOI: 10.1083/jcb.201001054
|View full text |Cite
|
Sign up to set email alerts
|

A ribosome-anchored chaperone network that facilitates eukaryotic ribosome biogenesis

Abstract: Ribosome-anchored proteins Jjj1 and Zuo1 function together with Hsp70 to mediate ribosome biogenesis (see also the companion paper from Koplin et al. in this issue).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(95 citation statements)
references
References 52 publications
4
89
2
Order By: Relevance
“…7E; Kaschner et al 2015). Both Jjj1 and RAC have also been implicated in early, nuclear steps of 60S subunit biogenesis, where they may play a role in prerRNA processing, unrelated to Arx1 recycling or nascent chain folding (Albanèse et al 2010). Even though further functional data are required to precisely define the nuclear roles of Jjj1-Ssa and RAC-Ssb, the available data suggest both architectural and functional overlap between these two ribosome-bound chaperone systems.…”
Section: Maturation Of the Central Protuberance And Checkpoint Contromentioning
confidence: 99%
“…7E; Kaschner et al 2015). Both Jjj1 and RAC have also been implicated in early, nuclear steps of 60S subunit biogenesis, where they may play a role in prerRNA processing, unrelated to Arx1 recycling or nascent chain folding (Albanèse et al 2010). Even though further functional data are required to precisely define the nuclear roles of Jjj1-Ssa and RAC-Ssb, the available data suggest both architectural and functional overlap between these two ribosome-bound chaperone systems.…”
Section: Maturation Of the Central Protuberance And Checkpoint Contromentioning
confidence: 99%
“…Later experiments carried out during a study of ribosome biogenesis demonstrated that Zuo1 had both a nuclear and a cytoplasmic localization (62). Deletion of ZUO1 produced a phenotype of slow growth at low temperature and sensitivity to salt, similar to that produced by double deletion of the chaperones Ssb1 and Ssb2.…”
Section: Zuotin a Cochaperone That Activates A Transcription Factormentioning
confidence: 99%
“…RAC also binds to ribosomes and is required for the interaction of Ssb with nascent chains (39)(40)(41). RAC/Ssb is connected to diverse cellular functions, including cotranslational folding (38,42,43), translational fidelity (44,45), and transcriptional regulation (46)(47)(48)(49). Recently, we found that RAC/Ssb also plays a role in the quality control of nonstop proteins and of model proteins that possess a bona fide stop codon but contain a C-terminal polylysine segment (termed polylysine proteins) (32).…”
mentioning
confidence: 99%